Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Get quick and reliable answers to your questions from a dedicated community of professionals on our platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Answer:
a = 1, b = - 12
Step-by-step explanation:
we know that x = 3 and x = - 4, so (x - 3) and (x + 4) must be the factors of the equation:
(x - 3)(x + 4)
x^2 + - 3x + 4x - 12
x^2 + x - 12
therefore a = 1 and b = - 12
Step-by-step explanation:
firstly substitute x=3 into [tex]x^{2} +ax+b=0[/tex]
[tex]3^{2} +3a+b=0[/tex]
9+3a+b = 0
b = -3a-9
secondly substitute x=-4 into [tex]x^{2} +ax+b=0[/tex]
[tex](-4)^{2} +(-4)a+b=0[/tex]
16-4a+b = 0
b = 4a-16
combine the equations above,
-3a-9 = b = 4a-16
so -3a-9 = 4a-16
7a = 7
a = 1
then substitute a = 1 into b = 4a-16 or b = -3a-9 (both are ok)
b = 4(1)-16 = -12 or b = -3(1)-9 = -12
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.